IDENTIFYING STUDENTS’ DIFFICULTIES IN UNDERSTANDING AND APPLYING PYTHAGOREAN THEOREM WITH AN ONTO-SEMIOTIC APPROACH - Rudi, Rudi; Suryadi, Didi; Rosjanuardi, Rizky (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Abstract: This research is conducted to obtain a description of students’ difficulties in understanding and applying Pythagorean theorem based on the onto-semiotic approach. This research applies a qualitative approach with phenomenology interpretation design. Research data were collected using test and interview methods. The research result was deducted from students’ answer sheets and interviews. Participants involved in this study were as many as 25 students of UPI Lab School Junior High School Bandung, who had learned Pythagorean theorem, 4 of which also participated in the interview. It showed that students found it complicated to comprehend definition, describe symbols or notations of mathematical objects, and interpret mathematical objects. Meanwhile, in solving problems related to the application of the Pythagorean theorem, students could describe procedure, algorithm, and technique in solving questions well. Abstrak: Penelitian ini bertujuan untuk mendapatkan gambaran kesulitan siswa dalam memahami dan menerapkan Teorema Pythagoras menggunakan pendekatan onto-semiotika. Penelitian ini menggunakan pendekatan kualitatif dengan desain interpretasi fenomenologi. Metode pengumpulan data, yaitu tes dan wawancara. Partisipan penelitian yang dilibatkan dalam uji kemampuan siswa adalah 25 orang siswa SMP Lab School UPI Bandung yang pernah belajar materi teorema Pythagoras, 4 orang dari 25 orang siswa tersebut dilibatkan dalam wawancara. Hasil penelitian menunjukkan bahwa siswa mengalami kesulitan dalam memahami definisi, mendeskripsikan simbol atau notasi dari objek matematika, serta kesulitan dalam memaknai objek matematika, sedangkan dalam menyelesaikan permasalahan penerapan teorema Pythagoras, siswa mampu mendeskripsikan prosedur, algoritma, dan teknik penyelesaikan masalah dengan baik.